The Role of IFN-β during the Course of Sepsis Progression and Its Therapeutic Potential - Rackov, Gorjana; Shokri, Rahman; De Mon, Melchor Álvarez; Martínez-A., Carlos; Balomenos, Dimitrios (Frontiers in Immunology, 2017)
Sepsis is a complex biphasic syndrome characterized by both pro- and anti-inflammatory immune states. Whereas early sepsis mortality is caused by an acute, deleterious pro-inflammatory response, the second sepsis phase is governed by acute immunosuppression, which predisposes patients to long-term risk for life-threatening secondary infections. Despite extensive basic research and clinical trials, there is to date no specific therapy for sepsis, and mortality rates are on the rise. Although IFN-β is one of the most-studied cytokines, its diverse effects are not fully understood. Depending on the disease or type of infection, it can have beneficial or detrimental effects. As IFN-β has been used successfully to treat diverse diseases, emphasis has been placed on understanding the role of IFN-β in sepsis. Analyses of mouse models of septic shock attribute a pro-inflammatory role to IFN-β in sepsis development. As anti-inflammatory treatments in humans with antibodies to TNF-α or IL1-β resulted disappointing, cytokine modulation approaches were discouraged and neutralization of IFN-β has not been pursued for sepsis treatment. In the case of patients with delayed sepsis and immunosuppression, there is a debate as to whether the use of specific cytokines would restore the deactivated immune response. Recent reports show an association of low IFN-β levels with the hyporesponsive state of monocytes from sepsis patients and after endotoxin tolerance induction. These data, discussed here, project a role for IFN-β in restoring monocyte function and reversing immunosuppression, and suggest IFN-β-based additive immunomodulatory therapy. The dichotomy in putative therapeutic approaches, involving reduction or an increase in IFN-β levels, mirrors the contrasting nature of the early hyperinflammatory state and the delayed immunosuppression phase.